Optimization of Battery Storage Systems in Solar Energy Application - BIN ABDULLAH, AMIRUL AJAI; Lam, Lam Hong Yin (Progress in Engineering Application and Technology, 2025)
Malaysia’s electrical grid is increasingly integrating renewable energy sources such as wind and solar power, which, while environmentally friendly, introduce challenges due to their intermittent and unpredictable energy supply. This variability can compromise grid stability and reliability, creating an urgent need for solutions that effectively balance energy demand and supply. Battery storage systems (BSS) emerge as promising technologies for addressing these challenges by storing surplus energy generated during high renewable energy production periods and releasing it during peak demand. This project focuses on optimizing the utilization of BSS within Malaysia’s renewable energy grid to enhance energy efficiency, reduce costs, and ensure grid stability. The proposed optimization framework leverages advanced techniques, including genetic algorithms, linear programming, and machine learning, to determine optimal charging and discharging schedules. The study also considers critical battery parameters, such as capacity, charge/discharge rates, and degradation over time, to maximize the lifespan and performance of the systems. In addition to technical optimization, the project evaluates the economic and environmental impacts of deploying BSS, aiming to achieve substantial cost savings, improved integration of renewable resources, and a more resilient energy grid. Furthermore, the project explores implementing advanced battery management systems (BMS) to facilitate real-time monitoring and control of energy flows. The expected outcomes include a scalable and adaptable BSS framework supporting Malaysia’s renewable energy goals. This project provides a forward-thinking approach to advancing Malaysia’s energy sustainability by leveraging cutting-edge optimization strategies and innovative battery technologies. Ultimately, this proposal highlights a pathway for Malaysia to strengthen its commitment to clean energy, address grid challenges, and create a versatile and energy-efficient renewable energy landscape.